The Mandatory Private Pension Pillar in Hungary: An Obituary - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2011)
In 1998, the left-of-center government of Hungary carved out a second pillar mandatory private pension system from the original mono-pillar public system. Participation in the mixed system was optional for those who were already working, but mandatory for new entrants to the workforce. About 50 per cent of the workforce joined voluntarily and another 25 per cent were mandated to do so by law between 1999 and 2010. The private system has not produced miracles: either in terms of the financial stability of the social security system, or greatly improved social security in old age. Moreover, the international financial and economic crisis has highlighted the transition costs of pre-funding. Rather than rationalizing the system, the current conservative government de facto "nationalized" the second pillar in 2011 and is to use part of the released capital to compensate for tax reductions.
Keywords: H55; J26; 330; social security reform; old age risk; defined contribution plan; privatization; political aspect; Hungary; Rentenreform; Private Altersvorsorge; Ungarn